A frogspawn-inspired hierarchical porous NaTi2(PO4)3–C array for high-rate and long-life aqueous rechargeable sodium batteries. Issue 44 (22nd October 2015) - Zhao, Baidan; Lin, Bo; Zhang, Sen; Deng, Chao
Abstract : A frogspawn-inspired hierarchical porous NaTi2 (PO4 )3 /C array exhibits superior high rate capability and ultralong cycling life as an anode for ARSB. Abstract : Hollow micro/nano-arrays have attracted tremendous attention in the field of energy conversion and storage, but such structures usually compromise the volumetric energy density of the electrode materials. Frogspawn consists of a spawn core and a transparent jelly shell organized in a hierarchical porous array, which exhibits superior mechanical strength and high-efficiency oxygen permeability. It can be used as a model for designing a new high-performance electrode material, which has advantages such as a high surface area, fast mass transport and superior durability. Herein, we report a frogspawn-like NaTi2 (PO4 )3 /C array prepared by a facile preform impregnation strategy. The framework is formed by a hollow carbon sphere connected by the NaTi2 (PO4 )3 /C skeleton, and its hollow is filled with the NaTi2 (PO4 )3 nanospheres. The whole hierarchical porous three-dimensional array copies the structure of a frogspawn. This unique structure not only enables easy electrolyte percolation and fast electron/ion transport, but also enhances the reversible capacity and cycling durability. When it is applied as an anode of the aqueous sodium ion battery, it exhibits favorable high rate capability and superior cycling stability, and retains 89% of the initial capacity after two thousand cycles at 20 C. Moreover, the full cell using the frogspawn-inspired NaTi2 (PO4 )3 –C as the anode and Na0.44 MnO2 as the cathode is capable of ultralong cycling up to one thousand cycles at alternate 10 and 60 C, which is among the best of state-of-the-art aqueous sodium ion systems. Therefore, the frogspawn-inspired architecture provides a new strategy to the tailored design of polyanion materials for high-power applications.